The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/nature13464
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for outer membrane lipopolysaccharide insertion

Abstract: Lipopolysaccharide (LPS) is essential for most Gram-negative bacteria and has crucial roles in protection of the bacteria from harsh environments and toxic compounds, including antibiotics. Seven LPS transport proteins (that is, LptA-LptG) form a trans-envelope protein complex responsible for the transport of LPS from the inner membrane to the outer membrane, the mechanism for which is poorly understood. Here we report the first crystal structure of the unique integral membrane LPS translocon LptD-LptE complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
291
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(311 citation statements)
references
References 44 publications
13
291
0
Order By: Relevance
“…Computational, mutagenesis and photo-crosslinking studies suggest that the lipid chains in LPS move along the hydrophobic cavity in the jelly-roll domain and exit into the outer leaflet of the OM through a transient lateral opening created between ß-strands-1 and -26 in the LptD ß-barrel domain. [9][10][11] A similar architecture is expected for the LptD/E complex from P. aeruginosa, except that sequence comparisons show that an additional ≈90-residue domain of unknown structure and function is inserted close to the N-terminus of the ß-jelly roll. This insert domain is a distinguishing feature of LptD in Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Computational, mutagenesis and photo-crosslinking studies suggest that the lipid chains in LPS move along the hydrophobic cavity in the jelly-roll domain and exit into the outer leaflet of the OM through a transient lateral opening created between ß-strands-1 and -26 in the LptD ß-barrel domain. [9][10][11] A similar architecture is expected for the LptD/E complex from P. aeruginosa, except that sequence comparisons show that an additional ≈90-residue domain of unknown structure and function is inserted close to the N-terminus of the ß-jelly roll. This insert domain is a distinguishing feature of LptD in Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the cellular processes by which LPS is assembled and transported to the outer membrane are essential for survival, and thus are targets for the development of new antibiotics. In two papers published on Nature's website today, Dong et al 1 and Qiao et al 2 present structural studies that disclose a remarkable molecular mechanism by which LPS arrives at its final destination in the outer membrane.…”
mentioning
confidence: 99%
“…However, LptE differs from BamB in structure, size (BamB: 40KDa, LptE: 20KDa), and location in relation to the central protein component. While BamB is known to interact with the periplasmic domains of BamA, LptE is situated within the central channel of LptD (Dong et al, 2014). In fact, the overall structure of LptE resembles a similar topology to that of the lipoprotein of BamE (Kim et al, 2011b).…”
Section: Growth Characteristics Of Mg1655 Periplasmic Chaperone Mutanmentioning
confidence: 99%
“…This suggests crucial interactions between Skp and the lipid membrane are important for outer membrane biogenesis. LPS is known to spontaneously insert into lipid membranes from aqueous solutions (Alam and Yamazaki, 2011 (Dong et al, 2014). Indeed, the lateral gate , Noinaj et al, 2013a conformational change simulated for BamA was also suggested for LptD (Dong et al, 2014).…”
Section: Growth Characteristics Of Mg1655 Periplasmic Chaperone Mutanmentioning
confidence: 99%
See 1 more Smart Citation